PENGARUH PENGGUNAAN ELECTRONIC BOOK TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TK TELKOM MAKASSAR - Nur Azizah Lestari; Sitti Nurhidayah Ilyas; Fitriani Dzulfadhilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The study aims to determine the effect of using Electronic Books on the speaking ability of children aged 5-6 years in Telkom Makassar Kindergarten. The research approach used is a quantitative approach with the type of experimental research with a post test only control group design research design. The population in this study is group B children aged 5-6 years in Telkom Makassar Kindergarten. The sampling in this study was simple random sampling. The sample in this study was 60 children with 30 children as the experimental group and 30 children as the control group. Data collection techniques use observation, tests and documentation. The data analysis techniques used are descriptive statistical analysis and parametric statistical analysis with the condition of normality test analysis, homogeneity test and hypothesis test. The results of the data analysis obtained by Asym (2-tailed) = 0.000 < 0.05 means that H1 is accepted and H0 is rejected thus the ability to speak in the experimental class is better than the control class, this proves that the use of electronic book media has a significant influence on the ability to speak in children aged 5-6 years at Telkom Makassar Kindergarten.